How the youth construct themselves in the context of PDI's youngblood written publication - Del Mundo, Teena Maribee A.
Using Jerome Bruner's Constructivism theory, this paper is about how the youth construct themselves through PDI's Youngblood written publication, the variable of specification were the forty-eight articles collected from January- December 2009 which were using a purposive sampling method. The study aims to seek the following questions: a.) Where does the youth derive their knowledge on the issue? b.) What is the hypothesis made? c.) What is the decision made about self-construct in the process of writing? As an approach to how the youth constructs themselves in the context of our society in Youngblood. This thesis paper which is founded on the basic assumption on the Constructivism theory of Jerome Bruner is socially relevant because: First, undoubtedly youth studies would contribute towards better rapport between adult and the younger generation. Another reason is to address the present situation of Youth's crisis. Just like other scholars, the researcher is eager to find out what creative experiments youth have done that could possibly improve the country by means of constructing and situating in the context of it. One way of doing it is to write about it. For mass media has become eye opener to arouse the consciousness of the general public about certain topics or issues. Using the spiral fatigue of Jerome Bruner's Constructive theory, the researcher analyzed each writer's source of existing knowledge on a particular issue. Following the next step in Jerome Bruner's framework of the Constructivism theory, the researcher analyzed the formulation of the article's hypothesis about a specific issue. After such a decision will be formulated based on the writer's stand in his/her article after undergoing the spiral of learning. After finding out what the decision of the writer in every article is, the researcher will deduce the self-construct of each writer by integrating the formulated decision into the process. In analyzing each 48 articles of Youngblood from January-December 2009, shows that the youth of today's generation are stepped in some traditional Filipino culture, media and of the orientation they were brought up to. There were evidences that in some articles, the process of self-construction varies from difference in culture trends in the kind of generation that these youth belongs to. Furthermore, the self constructs by the following author are as follows: Nationalistic ? because deciphered from the following articles it has the greater number of results which reflects that youth of today's generation were socially aware to their surrounding family oriented ? as part of Filipino tradition, the Filipino family has a distinctive characteristics to be more intimate towards each other. Filipino youth were also God fearing- being the only Christian in Asia. Filipino youth has been imparted by Family values to be such. They were also thankful, martyr for love, socially active in social networking as part of the advancement of technology in today's generation.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Media arts